2018
DOI: 10.2147/cmar.s159370
|View full text |Cite
|
Sign up to set email alerts
|

Effective prevention of sorafenib-induced hand–foot syndrome by dried-bonito broth

Abstract: BackgroundSorafenib (SOR) is a molecular medicine that prolongs the survival of patients with hepatocellular carcinoma (HCC). Therefore, the management of side effects is essential for the longer period of continuous medication. Among the various side effects, hand–foot syndrome (HFS) is the most common, occurring in 30%–50% of patients, and often results in discontinuation of the SOR medication. However, its mechanism has not been clarified, and no effective prevention method has been reported for the symptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…In addition, successful management in the HIS group, which tended to comprise cases with poorer hepatic reserve function, indicates that the combination of HIS with SOR may effectively prevent and manage clinical symptoms from toxicities induced by SOR. Regarding the effect of DBB and HIS on the antitumor effect of SOR, we have shown that DBB is effective for maintaining peripheral blood flow and preventing HFS induced by SOR treatment; in addition, no differences in tumor response were observed between the DBB group and the control group 4. This result is consistent with the results obtained with DBB and HIS in this study (Table 1).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In addition, successful management in the HIS group, which tended to comprise cases with poorer hepatic reserve function, indicates that the combination of HIS with SOR may effectively prevent and manage clinical symptoms from toxicities induced by SOR. Regarding the effect of DBB and HIS on the antitumor effect of SOR, we have shown that DBB is effective for maintaining peripheral blood flow and preventing HFS induced by SOR treatment; in addition, no differences in tumor response were observed between the DBB group and the control group 4. This result is consistent with the results obtained with DBB and HIS in this study (Table 1).…”
Section: Discussionsupporting
confidence: 90%
“…Bonito ( Katsuwonus pelamis ) is known as katsuo in Japan, where DBB is easy to obtain and is used to add flavor to food. In this study, the patients in the DBB group ingested 150 mL of commercially available, highly concentrated rich extract of DBB packs (Honzukuri Ichiban Dashi Kiwami Katsuo) orally, once a day every day, for the entire period of the study, in consistency with the previous study 4. The control group consumed normal food, which sometimes (one or two times a week) contained the extract; however, the concentration was approximately 10-fold lower than that in the pack.…”
Section: Methodsmentioning
confidence: 74%
See 2 more Smart Citations
“…Inhibition of platelet-derived growth factor receptors (PDGFRs) and c-Kit in the eccrine glands of the dermis and epidermis of the palms and soles may contribute to HFSR [22,23]. A decrease in peripheral blood flow following sorafenib treatment has also been linked to the emergence of this AE [24]. Hypertension may result from TKI inhibition of vascular endothelial growth factor (VEGF)-mediated nitric oxide synthase upregulation, thereby inhibiting vasomotor function and promoting degeneration of small blood vessels [25].…”
Section: Association Of Tki Aes With Positive Treatment Outcomesmentioning
confidence: 99%